Introduction: Finding Meaning on the Road to Hell - Wendy Ryden (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
SPECIAL SECTION: CREATIVE WRITING IN HIGHER EDUCATION: WHERE ARE WE GOING? WHERE HAVE WE BEEN? Introduction: Finding Meaning on the Road to Hell
Keywords: JAEPL